Pengaruh Lokasi, Citra Merek Dan Harga Terhadap Keputusan Pembelian (Studi kasus pada KonsumenMatahari Departemen Store Malang Town Square mahasiswa FEB Universitas Islam Malang) - M. Hasan Syaifoer Rizal; N. Rachma; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study analyzes the effect of Location, Brand Image and Price on Purchase Decisions. The population in this study was 18,500 respondents. The sample in this study was 100 respondents using accidental sampling technique.The results of this study note that the results of the F test are known that the location variable, brand image and price simultaneously have a significant effect on purchasing decisions. Purchase Keywords: Location, Brand Image and Price, Purchase Decision